2017
DOI: 10.1111/age.12529
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and patterns of population structure in Creole goats from the Americas

Abstract: Biodiversity studies are more efficient when large numbers of breeds belonging to several countries are involved, as they allow for an in-depth analysis of the within- and between-breed components of genetic diversity. A set of 21 microsatellites was used to investigate the genetic composition of 24 Creole goat breeds (910 animals) from 10 countries to estimate levels of genetic variability, infer population structure and understand genetic relationships among populations across the American continent. Three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 51 publications
4
29
1
3
Order By: Relevance
“…Although several studies have been carried out to characterise the genetic diversity of European, African, and South and Central American goats at the continental level (e.g. Cañón et al, 2006;Naderi et al, 2007;Ginja et al, 2017), a comprehensive joint analysis of breeds from the various continents has not been accomplished so far. Some research on New World goats has relied on mitochondrial DNA sequences (Amills et al, 2009), which reflect only the history of femalemediated gene flow and thus lack the power to track complex histories of introgression and admixture.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been carried out to characterise the genetic diversity of European, African, and South and Central American goats at the continental level (e.g. Cañón et al, 2006;Naderi et al, 2007;Ginja et al, 2017), a comprehensive joint analysis of breeds from the various continents has not been accomplished so far. Some research on New World goats has relied on mitochondrial DNA sequences (Amills et al, 2009), which reflect only the history of femalemediated gene flow and thus lack the power to track complex histories of introgression and admixture.…”
Section: Introductionmentioning
confidence: 99%
“…The approach of evaluating goats by this external phenotype has been validated by DNA testing, revealing that this phenotype, which occurs throughout the Americas, does reflect an underlying genotypic similarity. This indicates that the history and development of this type of goat traces back to a common foundation centuries ago [5,6].…”
Section: Spanish Goatmentioning
confidence: 85%
“…Research is now documenting that Spanish goats are generally superior to Boer goats in overall productivity measured on a herd-wide basis, and are on a par with Kiko goats [5,6]. This documentation points to the need to carefully evaluate local resources before replacing them with exotic resources, because local resources may indeed be equal or superior due to environmental adaptation.…”
Section: Spanish Goatmentioning
confidence: 99%
“…Similarly, a study investigating breed composition of Creole goats from 10 American countries found moderate to high heterozygosity values (Ginja et al . ).…”
Section: Discussionmentioning
confidence: 97%